Perancangan Sistem Informasi Pelayanan Publik (Menggunakan Metode RAD Pada Rukun Tetangga 010 Kebayoran Lama Utara) - Andhini Kamilla Puteri (CV. Multi Kreasi Media, 2024)
Rukun Tetangga is one of the organizations formed by the government to serve the needs of the community. One of the services in Rukun Tetangga 010 is managing citizen data and basic administration, for example the service for making Family Cards or KTPs. However, at this time the existing services in Rukun Tetangga 010 have not been maximized because they still use a manual system which is prone to loss, burning and time consuming. Therefore, this web-based public service information system can reduce the existing risks so that the service becomes easy and effective. In designing this public service information with UML, which includes Use Case Diagrams, Class Diagrams, Activity Diagrams and Sequence Diagrams. Built using the PHP programming language with MySql as a database using the RAD method. The final result of this research is that on this website residents can directly download the application letter.